213k views
24 votes
Simplify the expression:
1b+2c=3d

User Kabanus
by
5.8k points

2 Answers

0 votes

Answer:

b=3d-2c

Explanation:

Multiply b by 1.

Multiply b by 1.b+2c=3d

Multiply b by 1.b+2c=3dSubtract 2c from both sides of the equation.

Multiply b by 1.b+2c=3dSubtract 2c from both sides of the equation.b=3d−2c

User Jack Hughes
by
5.1k points
7 votes

Answer:

b=3d-2c

Explanation:

Multiply b by 1.

Multiply b by 1.b+2c=3d

Multiply b by 1.b+2c=3dSubtract 2c from both sides of the equation.

Multiply b by 1.b+2c=3dSubtract 2c from both sides of the equation.b=3d−2c

User Shak
by
6.2k points